Protective eraser, preparation method thereof and application of protective eraser in battery
By using silicone rubber-based protective rubber in lithium-ion batteries to absorb and disperse laser energy, the problem of thermal damage to the battery cells during laser welding is solved, and the safety and reliability of the battery are improved.
Patent Information
- Application Number
- CN202510772593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-09-19
AI Technical Summary
During the laser welding process of lithium-ion batteries, laser energy may penetrate the welding area and enter the interior of the battery, causing thermal damage to the battery cell material and affecting battery performance and safety. Existing technology cannot completely avoid this risk.
Silicone rubber is used as the skeleton material, and vulcanizers, structure control agents, thermal conductors, lubricants and ferrous oxide are added to form a three-dimensional thermal conductive network to absorb and disperse laser energy. A protective rubber sleeve is prepared and installed on the battery cell to block laser damage.
It effectively prevents damage to the battery cells caused by laser welding leaks during the laser welding process, improves the safety and reliability of the battery, and ensures the safety of the battery during strong impacts.
Smart Images

Figure CN120665436A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a protective rubber and a preparation method thereof and application in batteries. Background Art
[0002] With the widespread application of lithium-ion batteries in new energy vehicles, energy storage systems, consumer electronics and other fields, the safety and reliability of batteries have become the focus of industry attention. During the battery assembly process, the top cover and the shell are usually sealed and connected using a laser welding process to ensure the structural integrity and leakage-proof performance of the battery. However, the laser welding process has the characteristics of high energy density and strong penetration. If the laser parameters are not properly controlled or the welding path deviates, some laser energy may penetrate the welding area and enter the interior of the battery, causing thermal damage to the internal materials of the battery cell (such as diaphragms, electrodes, etc.). This damage will cause battery performance degradation, increase internal resistance, and even lead to safety hazards such as thermal runaway, seriously affecting the cycle life and safety of the battery.
[0003] Currently, the industry primarily aims to reduce the impact of lasers on battery cells by optimizing laser welding parameters (such as power, frequency, and focal length) or improving welding path design. However, these methods require extremely high process precision and are difficult to completely avoid the risk of laser energy leakage. Therefore, there is an urgent need for a simple, efficient, and performance-neutral protective measure that can effectively block or absorb scattered laser energy during laser welding to prevent thermal damage to the internal materials of the battery cell. Summary of the Invention
[0004] To address the aforementioned issues, the present invention provides a protective rubber, a preparation method thereof, and its application in batteries. The present invention utilizes silicone rubber as a skeleton material and incorporates appropriate amounts of a vulcanizing agent, a structure-controlling agent, a thermal conductor, a lubricant, a surfactant, and ferrous oxide. Under the action of the vulcanizing agent, the linear molecular chains of the silicone rubber are crosslinked to form a network structure. Simultaneously, under the action of the surfactant, the thermal conductor and the lubricant, which absorbs light and conducts heat, are uniformly dispersed within the rubber matrix to form a three-dimensional thermal network. This synergistic effect of the ferrous oxide converts laser light into heat energy, which is then dispersed through the three-dimensional thermal network. Furthermore, the addition of an appropriate amount of the structure-controlling agent improves the rubber's workability and heat resistance after long-term storage. The synergistic effect of these ingredients results in a protective rubber with high laser absorption and excellent thermal conductivity. The rubber can be processed into a ring-shaped rubber component and fitted over the upper end surface of a battery cell, effectively preventing damage to the cell from laser welding leaks.
[0005] The present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a protective rubber, which contains the following raw materials in parts by mass: 100 parts of silicone rubber, 1.5-1.8 parts of a vulcanizing agent, 2-4 parts of a structure control agent, 30-35 parts of a thermal conductor, 50-60 parts of a lubricant, 5-10 parts of a surfactant, and 3-5 parts of ferrous oxide; the lubricant has light absorption and heat conduction effects.
[0007] Furthermore, the molecular weight of the silicone rubber is 60×10 4 -70×10 4 The molar fraction of vinyl segments in the silicone rubber is 0.13%-0.18%.
[0008] Furthermore, the vulcanizing agent may be selected from one or more of 2,4-dichlorobenzoyl peroxide, dicumyl peroxide and bis-(tert-butyl isopropyl peroxide)benzene.
[0009] Furthermore, the structure control agent may be selected from one or more of diphenylsilanediol, methyltriethoxysilane and hydroxy silicone oil.
[0010] Furthermore, the thermal conductor is selected from one or more of aluminum nitride, silicon carbide and boron nitride.
[0011] Furthermore, the lubricant is graphite powder and / or molybdenum disulfide.
[0012] Furthermore, the surfactant is preferably zinc stearate.
[0013] Furthermore, the protective rubber comprises the following raw materials in parts by mass: 100 parts of silicone rubber, 1.6 parts of 2,4-dichlorobenzoyl peroxide, 3 parts of diphenylsilanediol, 30-35 parts of aluminum nitride, 50-60 parts of graphite powder, 8 parts of zinc stearate, and 4 parts of ferrous oxide.
[0014] A second aspect of the present invention provides a method for preparing the protective rubber according to the first aspect, comprising the following steps:
[0015] S1. Evenly mix the vulcanizing agent and part of the silicone rubber to obtain a vulcanizing agent masterbatch;
[0016] The remaining silicone rubber is mixed with a structure control agent, a surfactant, and ferrous oxide for a first time, and then a thermal conductive agent and a lubricant are added for a second mixing to obtain a first rubber compound, which is filtered to remove impurities and then calendered to obtain a film;
[0017] S2, mixing the vulcanizing agent masterbatch prepared in S1 with the rubber for the third time to obtain a second rubber compound, and calendering the second rubber compound to obtain the protective rubber.
[0018] Furthermore, in step S1, the mass ratio of the vulcanizing agent to the part of the silicone rubber is 1:(2.5-3); preferably, the vulcanizing agent and the part of the silicone rubber are mixed in an open mill, and the mixing time is 10-12 minutes.
[0019] Furthermore, in step S1, the first mixing and the second mixing are both performed in an internal mixer, and the rotation speed of the internal mixer is 25-30 r / min.
[0020] Furthermore, in step S1, the temperature of the first mixing and the second mixing are both 130-140°C.
[0021] Furthermore, in step S1, in the first mixing step: firstly, the remaining silicone rubber is mixed for 1-1.5 minutes, and then the structure control agent, surfactant and ferrous oxide are added and mixed for 1.0-1.2 minutes.
[0022] Furthermore, in step S1, the second mixing time is preferably 2.5-3.5 minutes.
[0023] Furthermore, in step S1, a three-roll calender is used to calender the first rubber material after filtering and removing impurities to obtain the film; more preferably, the thickness of the film is 1.2-1.5 mm.
[0024] Furthermore, the preparation method further comprises subjecting the film to a static treatment before the third mixing, and the static treatment time is preferably 8-24 hours.
[0025] Furthermore, in step S2, the third mixing is performed in an internal mixer, and the rotation speed of the internal mixer is preferably 20-25 r / min.
[0026] Furthermore, in step S2, the temperature of the third mixing is preferably 100-120°C.
[0027] Furthermore, in step S2, in the third mixing step: firstly, the film is mixed for 1-2 minutes, and then the vulcanizing agent masterbatch is added and mixed for 0.8-1 minute.
[0028] Furthermore, in step S2, a three-roll calender is used to calender the second rubber material to obtain the protective rubber.
[0029] A third aspect of the present invention provides a battery comprising the protective rubber described in the first aspect or the protective rubber prepared by the preparation method described in the second aspect.
[0030] Furthermore, the battery comprises:
[0031] A battery cell, wherein the edges of the upper end surface of the battery cell are sleeved with an annular rubber member, and the annular rubber member is made of the protective rubber;
[0032] a shell, for accommodating the battery cell, wherein the shell has an opening;
[0033] A top cover is welded to the shell to close the opening.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention provides a protective rubber having silicone rubber as a skeleton material. Under the action of a vulcanizing agent, the linear molecular chains of the silicone rubber are cross-linked to form a network structure, thereby improving the physical and mechanical properties of the rubber matrix. In addition, under the action of a surfactant, an introduced thermal conductor and a lubricant with light-absorbing and heat-conducting properties are uniformly dispersed in the rubber matrix to form a three-dimensional heat-conducting network. The three-dimensional heat-conducting network cooperates with the photothermal conversion effect of ferrous oxide to convert laser light into heat energy and disperse it through the three-dimensional heat-conducting network, thereby achieving a high absorption rate of the laser light, reducing the intensity of the transmitted laser light, and enabling rapid heat conduction and dispersion to avoid local overheating. In addition, by adding an appropriate amount of a structure control agent, the rubber material containing a large amount of filler can be effectively prevented from experiencing a decrease in plasticity during storage and gradually losing its refining and processing performance during structuring, thereby ensuring the workability and heat resistance of the rubber material after long-term storage. With the synergistic effect of the above-mentioned raw materials, the prepared protective rubber structure is load-bearing and has strong resistance to laser damage. It can be processed into a ring-shaped rubber part and installed on the upper end surface of the battery cell. It can not only effectively prevent the damage to the battery cell caused by laser welding defects during laser welding, but also use its high resilience to absorb impact stress when the battery is subjected to strong impact, thereby protecting the battery safety.
[0036] 2. The present invention also provides a method for preparing protective rubber. By mixing the masterbatch in three stages, the raw materials can be evenly mixed. This not only helps to further improve the thermal conductivity, laser absorptivity, and ablation resistance of the rubber, and reduce laser transmittance, but also ensures the consistency of the performance of rubber prepared in different batches, which is beneficial to rubber quality control and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic structural diagram of an annular rubber component provided by the present invention;
[0038] Figure 2 This is a schematic diagram of the structure of a battery cell provided by the present invention, in which an annular rubber member is sleeved on the edges of the upper end surface;
[0039] Figure 3 This is a schematic diagram of a local structure of a battery according to the present invention;
[0040] In the figure: 01 is the battery cell, 02 is the ring-shaped rubber part, and 03 is the top cover. DETAILED DESCRIPTION
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the relevant listed items. The term "includes" or "comprising" described in the present invention means that in addition to the components described, it may also include or contain other components. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0042] As described in the background, during battery assembly, the top cover and casing are typically sealed using laser welding to ensure the battery's structural integrity and leak-proof performance. Laser welding offers high energy density and strong penetration. However, improper laser parameter control or deviations in the welding path can cause some laser energy to penetrate the weld area and enter the battery interior, causing thermal damage to the cell's internal materials. This damage can cause battery performance degradation, increase internal resistance, and even lead to safety hazards such as thermal runaway, seriously impacting the battery's cycle life and safety.
[0043] In order to solve the above problems, the embodiments of the present invention provide a protective rubber that can effectively block or absorb scattered laser energy during laser welding to prevent the laser from leaking into the interior of the battery and causing thermal damage to the internal materials of the battery cell; specifically, the protective rubber comprises the following raw materials in parts by mass: 100 parts of silicone rubber, 1.5-1.8 parts of vulcanizing agent (for example, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, etc.), 2-4 parts of structural control agent (for example, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, etc.), 100 parts of silicone rubber, ... 3.6 parts, 3.8 parts, 4 parts, etc.), 30-35 parts of thermal conductor (for example, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, etc.), 50-60 parts of lubricant (for example, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, etc.), 5-10 parts of surfactant (for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.), 3-5 parts of ferrous oxide (for example, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.); the lubricant has light absorption and heat conduction effects.
[0044] Furthermore, the lubricant is graphite powder and / or molybdenum disulfide, which acts as a lubricant and has thermal conductivity, and can significantly improve the thermal conductivity and processing performance of the rubber material.
[0045] To solve the problem of laser welding defects during battery assembly, the present invention provides a protective rubber that is resistant to laser damage. By using silicone rubber as the skeleton material and adding appropriate amounts of a vulcanizing agent, a structure control agent, a thermal conductor, a lubricant, a surfactant, and ferrous oxide, the synergistic effect of the above components produces a rubber material with high laser absorption efficiency, good thermal conductivity, excellent ablation resistance, and good processing performance.
[0046] Specifically:
[0047] The present invention uses silicone rubber that is resistant to high and low temperatures, has good elasticity and good thermal conductivity as a skeleton material to ensure the high thermal conductivity of the rubber and its applicability in harsh environments. To further improve the physical and mechanical properties of the rubber, an appropriate amount of vulcanizing agent is added so that the rubber molecular chains in the silicone rubber can cross-link to form a network structure at the vulcanization temperature. The cross-linked network structure can inhibit the thermal motion of the molecular chains, thereby further improving the high-temperature resistance of the silicone rubber. At the same time, to avoid the introduction of excessive vulcanizing agent, which leads to increased brittleness of the material and affects the processability and elasticity of the rubber, the amount of vulcanizing agent added needs to be controlled within an appropriate range, such as the aforementioned 1.5-1.8 parts per 100 parts of silicone rubber. In addition, the present invention introduces an appropriate amount of thermal conductive agent and a specific lubricant with a layered structure into the rubber material. On the one hand, the introduction of the lubricant can improve the dispersibility of the thermal conductive agent, which is beneficial to improving the processing performance of the rubber material. At the same time, under the action of the surfactant, the uniformity of the system can be further improved, so that the thermal conductive agent and the lubricant with light absorption and heat conduction can be evenly dispersed in the rubber material and form a three-dimensional heat conduction network, thereby improving the thermal conductivity of the rubber. However, excessive addition of thermal conductive agent and lubricant will affect the mechanics of silicone rubber, and excessive addition will make it difficult for the thermal conductive agent and lubricant to be evenly distributed in the silicone rubber. Dispersion is easy to occur and agglomeration occurs, which in turn leads to the blocking of the heat conduction path and the reduction of the thermal conductivity of the rubber. Therefore, the addition amount of thermal conductor and lubricant needs to be controlled within an appropriate range. For example, 30-35 parts of thermal conductor and 50-60 parts of lubricant are added to every 100 parts of silicone rubber. In order to ensure the dispersion of thermal conductor and lubricant in silicone rubber while avoiding the introduction of excessive surfactants that affect other properties of the rubber (such as mechanical properties, processing properties, etc.), the content of surfactant needs to be controlled within an appropriate range, for example, 5-10 parts of surfactant / 100 parts of silicone rubber.
[0048] The protective rubber protected by the present invention also incorporates an appropriate amount of ferrous oxide. This addition not only improves the aging resistance and heat resistance of the silicone rubber, but more importantly, unlike other antioxidants or thermal conductors, ferrous oxide has a high absorption coefficient in the near-infrared to visible wavelength range (the laser wavelength used for welding the top cover and the housing in conventional battery assembly processes is typically within this range, e.g., 1064 nm). It absorbs photon energy and converts it into heat energy, which is rapidly dispersed through the three-dimensional heat-conducting network, thereby achieving a high laser absorption rate, reducing the transmitted laser intensity, and avoiding local overheating. However, the amount of ferrous oxide added must be controlled within an appropriate range. Too little addition results in poor laser absorption, while too much addition can easily lead to aggregation, which can easily cause local overheating under laser irradiation. Therefore, the amount of ferrous oxide added must be controlled within an appropriate range, i.e., 3-5 parts ferrous oxide per 100 parts silicone rubber.
[0049] Furthermore, by adding an appropriate amount of a structure control agent, the present invention effectively prevents the plasticity loss and gradual loss of refining and processing properties of rubber materials containing large amounts of fillers during storage, thereby ensuring the rubber's workability and heat resistance after long-term storage. However, if an excessive amount of a structure control agent is added to silicone rubber, it will hinder the reaction between the vulcanizer and the rubber molecular chains, affecting vulcanization efficiency, and will damage the interface between the filler and the rubber, affecting mechanical properties. Therefore, the content of the structure control agent must be controlled within an appropriate range, such as the aforementioned 2-4 parts structure control agent per 100 parts silicone rubber.
[0050] Under the synergistic effect of the above raw materials, the prepared protective rubber structure is load-bearing and has strong resistance to laser damage, good processability, and is suitable for laser protection in different scenarios.
[0051] In the present invention, the molecular weight of the silicone rubber is preferably 60×10 4 -70×10 4 , and the molar fraction of the vinyl chain in the silicone rubber is preferably 0.13%-0.18%. The vinyl content in the silicone rubber will affect the vulcanization activity and processing safety. The vulcanization activity of the silicone rubber is improved as much as possible while ensuring processing safety. Preferably, the molar fraction of the vinyl chain in the silicone rubber is controlled in the range of 0.13%-0.18%; in some preferred embodiments, the 110-2 silicone rubber of Kandis Chemical (Hubei) Co., Ltd. is used.
[0052] In the present invention, the vulcanizing agent can be selected from one or more of 2,4-dichlorobenzoyl peroxide, diisopropyl benzene peroxide and bis-(tert-butyl peroxyisopropyl)benzene; more preferably, 2,4-dichlorobenzoyl peroxide has high vulcanization efficiency and low vulcanization temperature, which is beneficial to energy saving and consumption reduction.
[0053] In the present invention, the structure control agent may be selected from one or more of diphenylsilanediol, methyltriethoxysilane and hydroxy silicone oil.
[0054] In the present invention, the thermal conductive agent can be selected from one or more of aluminum nitride, silicon carbide and boron nitride. Such thermal conductive agents have high thermal conductivity and can significantly improve the thermal conductivity of the rubber material.
[0055] In the present invention, the surfactant is preferably zinc stearate, which can activate the surface of fillers such as aluminum nitride, help disperse the fillers, and make the performance of the rubber more uniform. In addition, it has excellent slipperiness, can improve the fluidity of the rubber, improve the surface quality, and enhance the finish.
[0056] In some preferred embodiments of the present invention, the protective rubber comprises the following raw materials in parts by mass: 100 parts of silicone rubber, 1.6 parts of 2,4-dichlorobenzoyl peroxide, 3 parts of diphenylsilanediol, 30-35 parts of aluminum nitride, 50-60 parts of graphite powder, 8 parts of zinc stearate, and 4 parts of ferrous oxide.
[0057] The embodiment of the present invention also provides a method for preparing the protective rubber, comprising the following steps:
[0058] S1. Evenly mix the vulcanizing agent and part of the silicone rubber to obtain a vulcanizing agent masterbatch;
[0059] The remaining silicone rubber is mixed with a structure control agent, a surfactant, and ferrous oxide for a first time, and then a thermal conductive agent and a lubricant are added for a second mixing to obtain a first rubber compound, which is filtered to remove impurities and then calendered to obtain a film;
[0060] S2, mixing the vulcanizing agent masterbatch prepared in S1 with the rubber for the third time to obtain a second rubber compound, and calendering the second rubber compound to obtain the protective rubber.
[0061] In the preparation process of the protective rubber of the present invention, the mixing process of the masterbatch is divided into three stages: the first stage of masterbatch preparation, in which part of the silicone rubber is mixed with the vulcanizing agent to prepare the vulcanizing agent masterbatch, so as to ensure that the vulcanizing agent is more evenly dispersed; the second stage of mixing, in which the remaining silicone rubber is mixed with the structure control agent, surfactant, and ferrous oxide for the first time, and then the thermal conductive agent and lubricant are added for the second mixing, so as to avoid the addition of the thermal conductive agent, lubricant and fillers such as the structure control agent together, which leads to a significant increase in the viscosity of the rubber and the problem of uneven mixing; after filtering the rubber, the rubber is rolled into a film; the third stage is sulfur addition, in which the film is mixed with the vulcanizing agent masterbatch to form a mixed film, which is cooled and stored for use. The present invention performs masterbatch mixing in three stages, so that the raw materials are fully and evenly mixed, which not only helps to further improve the thermal conductivity, laser absorption rate, ablation resistance and reduce laser transmittance of the rubber, but also ensures the consistency of the performance of rubbers prepared in different batches, which is conducive to rubber quality control and is suitable for industrial production.
[0062] In some preferred embodiments of the present invention, the mass ratio of the vulcanizing agent to the portion of the silicone rubber in step S1 is 1:(2.5-3), for example, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3.0, etc., including but not limited to the mass ratios listed above; more preferably, the vulcanizing agent and the portion of the silicone rubber are mixed in an open mill, and the mixing time is preferably 10-12 min.
[0063] In some preferred embodiments of the present invention, the first mixing and the second mixing in step S1 are both carried out in an internal mixer, and the rotation speed of the internal mixer is preferably 25-30 r / min; more preferably, the temperature of the first mixing and the second mixing is 130-140°C. Mixing at the above rotation speed and temperature is beneficial to removing moisture and small molecular volatiles in the material, and can prevent rubber degradation caused by excessive temperature.
[0064] In some preferred embodiments of the present invention, in the first mixing step: first, the remaining silicone rubber is mixed for 1-1.5 minutes, and then the structure control agent, surfactant, and ferrous oxide are added and mixed for 1.0-1.2 minutes; the second mixing time is preferably 2.5-3.5 minutes.
[0065] In some preferred embodiments of the present invention, in step S1, a three-roll calender is used to calender the first rubber material after filtering and removing impurities to obtain the film; more preferably, the thickness of the film is controlled within the range of 1.2-1.5 mm.
[0066] In some preferred embodiments of the present invention, the above-mentioned preparation method also includes subjecting the film to a standing treatment before the third mixing to improve the uniformity of the distribution of the components inside the rubber material (during operations such as calendering, some components in the rubber material may be unevenly distributed due to uneven forces, and the standing treatment can provide time for the components inside the rubber material to be redistributed). The standing treatment time is preferably 8-24 hours, for example 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, etc., including but not limited to the standing times listed above.
[0067] In some preferred embodiments of the present invention, the third mixing in step S2 is performed in an internal mixer, and the speed of the internal mixer is preferably 20-25 r / min. More preferably, the temperature of the third mixing is preferably 100-120° C. Compared with the first and second mixing, the third mixing is performed at a slower speed and lower temperature to prevent scorching of the rubber material and ensure the quality of the rubber material.
[0068] In some preferred embodiments of the present invention, in the third mixing step: firstly, the film is mixed for 1-2 minutes, and then the vulcanizing agent masterbatch is added and mixed for 0.8-1 minute.
[0069] In some preferred embodiments of the present invention, in step S2, a three-roll calender is used to calender the second rubber material to obtain the protective rubber.
[0070] In the present invention, the prepared protective rubber needs to be stored for at least 24 hours before being used for molding. On the one hand, the long-term storage allows the vulcanizer, activator, antioxidant and other additives in the rubber material to be further evenly dispersed; on the other hand, the stress generated by the mixing process is also eliminated, which is beneficial to the molding process and the improvement of performance.
[0071] In addition, the embodiments of the present invention provide a battery comprising the protective rubber described above; in some preferred embodiments, the battery comprises:
[0072] A battery cell, wherein the edges of the upper end surface of the battery cell are sleeved with an annular rubber member, and the annular rubber member is made of the protective rubber;
[0073] a shell, for accommodating the battery cell, wherein the shell has an opening;
[0074] A top cover is welded to the shell to close the opening.
[0075] The present invention processes the protective rubber into an annular rubber part and sets it on the upper end surface of the battery cell. It can not only effectively prevent the battery cell from being damaged by laser welding leaks during laser welding, but also use its high resilience to absorb impact stress when the battery is subjected to strong impact, thereby protecting the battery safety.
[0076] The present invention will be further described below with reference to specific embodiments and accompanying drawings so that those skilled in the art can better understand and implement the present invention. However, the embodiments are not intended to limit the present invention.
[0077] Example 1
[0078] This embodiment relates to the preparation of a protective rubber, and the specific steps are as follows:
[0079] (1) Preparation of curing agent masterbatch: 3 parts of curing agent 2,4-dichlorobenzoyl peroxide (DCPB) and 9 parts of silicone rubber (Kandis Chemical (Hubei) Co., Ltd. 110-2 type) were mixed in an open mill for 10 minutes, and after making 6 triangular bags, the pieces were removed and stored for preparation;
[0080] (2) After adding 91 parts of silicone rubber and mixing for 1.5 minutes, 3 parts of diphenylsilanediol, 4 parts of ferric oxide and 8 parts of zinc stearate were added and mixed in a meshing type internal mixer for the first time. The internal mixer rotor speed was 25r / min, the mixing temperature was 130°C, and the mixing time was 1.0min. Then 35 parts of aluminum nitride and 50 parts of graphite powder were added for the second mixing. The mixing time was 2.5min. The mixed mixture was added to a rubber filter and filtered with a 60-mesh stainless steel filter to remove impurities. Then, the filtered rubber was rolled into a film with a thickness of 1.2mm using a three-silver calender and stored for 10 hours.
[0081] (3) The stored rubber sheet is added to an internal mixer and kneaded for 2 minutes, and then the vulcanizing agent masterbatch is added. The kneading time is 0.8 minutes, the rotor speed of the internal mixer is 20 r / min, and the kneading temperature is 100°C; the vulcanized and kneaded rubber material is then rolled on a three-roll calender to form a strip of rubber sheet with a thickness of 0.8-1.0 mm and a width of 150-160 mm, thus obtaining a protective rubber.
[0082] Example 2
[0083] This embodiment relates to the preparation of a protective rubber, which differs from Example 1 only in that the amount of aluminum nitride added is 32.5 parts and the amount of graphite powder added is 55 parts; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0084] Example 3
[0085] This embodiment relates to the preparation of a protective rubber, which differs from Example 1 only in that the amount of aluminum nitride added is 30 parts and the amount of graphite powder added is 60 parts; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0086] Comparative Example 1
[0087] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that no aluminum nitride is added; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0088] Comparative Example 2
[0089] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that no graphite powder is added; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0090] Comparative Example 3
[0091] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that no aluminum nitride and graphite powder are added; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0092] Comparative Example 4
[0093] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that the amount of graphite powder added is 70 parts; the other raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0094] Comparative Example 5
[0095] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that the amount of aluminum nitride added is 50 parts; the other raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0096] Comparative Example 6
[0097] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that an equal amount of barium stearate is used instead of graphite powder; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0098] Comparative Example 7
[0099] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that an equal amount of N-phenyl-N'-isopropyl-p-phenylenediamine is used instead of ferrous oxide; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0100] Comparative Example 8
[0101] This comparative example relates to the preparation of a protective rubber, which differs from Example 1 only in that: in step (2), aluminum nitride and graphite powder are added together with diphenylsilanediol, ferrous oxide, and zinc stearate for mixing; the remaining raw material contents and preparation processes are the same, and the corresponding protective rubber is prepared.
[0102] Performance Testing
[0103] The protective rubbers prepared in the above embodiments and comparative examples were subjected to the following performance tests, as follows:
[0104] Preparation of test samples: The protective rubbers prepared in the above embodiments and comparative examples were immersed in an electrolyte (ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then fully dried lithium salt LiPF6 was dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.) for 5 hours, taken out, wiped the surface, and baked in an oven at 100°C for 2 hours before performance measurement.
[0105] Thermal conductivity test: 1. Sample preparation: Make sure the sample size meets the test requirements and measure the thickness with a vernier caliper, accurate to 0.01mm. 2. Test environment: Control the laboratory temperature at 23±2℃ and the humidity at 50±5%. 3. Install the sample: Place the sample between two parallel metal plates, with good contact between the metal plates and the sample, and ensure uniform pressure between the sample and the metal plates. 4. Set parameters: Set the heating plate to 80℃ and the heat sink to 20℃. Start measuring after the temperature reaches a stable state. Keep the temperature stable during the measurement process. 5. Measurement and calculation: Use a heat flow meter to measure the heat flow through the sample and measure the temperature difference on both sides of the sample at the same time. According to Fourier's law, thermal conductivity k = Q×d / (A×ΔT), where Q is the heat flow, d is the sample thickness, A is the sample area, and ΔT is the temperature difference.
[0106] Ablation threshold test: 1. Experimental material preparation: Select appropriate materials for mounting. 2. Experimental setup: Use a video microscope to determine the laser spot position and adjust the displacement processing platform. 3. Experimental condition setting: Set the laser power density point to 0.1-50J / cm2, with a step size of 0.5J / cm2. The pulse frequency of single-pulse ablation can be set to approximately 1kHz. 4. Experimental process: Conduct single-pulse or multi-pulse ablation experiments and record the ablation effect. 5. Data analysis: Calculate the ablation threshold by measuring the single-pulse ablation pit diameter corresponding to different laser powers.
[0107] Transmittance, reflectance and absorptivity test (tested by transmission spectrometer):
[0108] 1. Prepare the sample: Prepare the rubber sample with a thickness of 2 mm and an area of 10 × 10 mm 2 , and the surface is flat and smooth, without bubbles, scratches and other defects.
[0109] 2. Set the instrument parameters: set the wavelength range to 200-700nm and measure every 10nm.
[0110] 3. Transmittance Test: Use air (100% transmittance) as a standard substance for transmittance calibration to ensure instrument accuracy. Measure the incident light intensity (with air as the background). Then, place the sample in the sample cell and measure the transmitted light intensity. Calculate the transmittance: Calculate the transmittance using the formula T = I / I0, where T is the transmittance, I is the transmitted light intensity, and I0 is the incident light intensity.
[0111] Reflectivity test: Use a polytetrafluoroethylene standard as a standard substance for reflectivity calibration to ensure the instrument's measurement precision and accuracy. Place the sample in the sample cell and measure the reflected light intensity while simultaneously recording the incident light intensity (with air as the background). Calculate the reflectivity using the formula R = I / I0, where R is the reflectivity, I is the reflected light intensity, and I0 is the incident light intensity.
[0112] Absorption rate calculation: The absorption rate is calculated according to the formula A=1-RT, where A is the absorption rate, R is the reflectivity, and T is the transmittance.
[0113] The test results are shown in Table 1 below:
[0114] Table 1
[0115]
[0116]
[0117] As shown in Table 1, the protective rubbers prepared in Examples 1-3 have high thermal conductivity, high ablation threshold, and high laser absorptivity, and low transmittance and reflectivity, and can be used to prevent laser damage.
[0118] As shown in Example 1 and Comparative Examples 1-3, the addition of aluminum nitride and graphite powder significantly improves the thermal conductivity, ablation resistance, and light absorption rate of the rubber material. In particular, when the graphite powder component is absent, the thermal conductivity and ablation resistance of the rubber material significantly decrease. This is because the lack of graphite powder, which has both thermal conductivity and lubrication properties, prevents the construction of a three-dimensional thermal conductive network, significantly reducing the thermal conductivity of the rubber material. In contrast, rubber materials prepared by increasing the content of aluminum nitride (Comparative Example 4) or graphite powder (Comparative Example 5) show a significant decrease in thermal conductivity and ablation threshold. This is because high levels of aluminum nitride and graphite powder make it difficult to evenly disperse in the silicone rubber and easily agglomerate, resulting in a blocked heat conduction pathway, a decrease in thermal conductivity, and a negative impact on light absorption.
[0119] Furthermore, as shown in Example 1 and Comparative Examples 6 and 7, the layered, thermally conductive lubricant (graphite powder) in the protective rubber prepared by the present invention cannot be replaced by other lubricants. For example, in Comparative Example 6, barium stearate is used instead of graphite. However, barium stearate is relatively more susceptible to the effects of acids, alkalis, and other substances, resulting in damage to the rubber material's performance after immersion in electrolyte. Furthermore, barium stearate cannot form a three-dimensional thermally conductive network structure with the thermally conductive agent and has a low light absorption rate, significantly affecting the rubber material's thermal conductivity and light absorption. Other antioxidants are also not suitable for replacing ferrous oxide. For example, in Comparative Example 7, an equal amount of N-phenyl-N'-isopropyl-p-phenylenediamine is used. Compared to Example 1, the thermal conductivity, ablation resistance, and light absorption rate of the resulting rubber material are all reduced. This is because the ferrous oxide in the protective rubber prepared by the present invention, while acting as an antioxidant, also helps improve the rubber material's thermal conductivity and light absorption.
[0120] In addition, it can be seen from Example 1 and Comparative Example 8 that in the process of preparing the rubber material, the order of adding the fillers will affect the performance of the product. In Comparative Example 8, by adding aluminum nitride and graphite powder together with fillers such as diphenylsilanediol, the viscosity of the mixed material increases and the fluidity deteriorates, resulting in problems such as difficulty in stirring and uneven mixing during the processing, which reduces the performance of the prepared rubber.
[0121] The above-described embodiments are merely preferred examples for the purpose of fully illustrating the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
Claims
1. A protective rubber, characterized in that: The protective rubber comprises the following raw materials in parts by mass: 100 parts of silicone rubber, 1.5-1.8 parts of vulcanizing agent, 2-4 parts of structure control agent, 30-35 parts of thermal conductor, 50-60 parts of lubricant, 5-10 parts of surfactant, and 3-5 parts of ferrous oxide; the lubricant has light absorption and heat conduction functions.
2. The protective rubber according to claim 1, characterized in that Contain at least one of the following characteristics: (1) The molecular weight of the silicone rubber is 60×10 4 -70×10 4 , the mole fraction of vinyl chain segments in the silicone rubber is 0.13%-0.18%; (2) The vulcanizing agent is selected from one or more of 2,4-dichlorobenzoyl peroxide, diisopropylbenzene peroxide and bis-(tert-butyl isopropyl peroxide)benzene; (3) the structure control agent is selected from one or more of diphenylsilanediol, methyltriethoxysilane and hydroxy silicone oil; (4) The thermal conductor is selected from one or more of aluminum nitride, silicon carbide and boron nitride; (5) The lubricant is graphite powder and / or molybdenum disulfide; (6) The surfactant is zinc stearate.
3. The protective rubber according to claim 2, characterized in that: The protective rubber comprises the following raw materials in parts by mass: 100 parts of silicone rubber, 1.6 parts of 2,4-dichlorobenzoyl peroxide, 3 parts of diphenylsilanediol, 30-35 parts of aluminum nitride, 50-60 parts of graphite powder, 8 parts of zinc stearate, and 4 parts of ferrous oxide.
4. A method for preparing the protective rubber according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Evenly mix the vulcanizing agent and part of the silicone rubber to obtain a vulcanizing agent masterbatch; The remaining silicone rubber is mixed with a structure control agent, a surfactant, and ferrous oxide for a first time, and then a thermal conductive agent and a lubricant are added for a second mixing to obtain a first rubber compound, which is filtered to remove impurities and then calendered to obtain a film; S2, mixing the vulcanizing agent masterbatch prepared in S1 with the rubber for the third time to obtain a second rubber compound, and calendering the second rubber compound to obtain the protective rubber.
5. The preparation method according to claim 4, characterized in that In step S1, the mass ratio of the vulcanizing agent to the portion of the silicone rubber is 1:(2.5-3); The vulcanizing agent and part of the silicone rubber are mixed in an open mill, and the mixing time is 10-12 minutes.
6. The preparation method according to claim 4, characterized in that In step S1, at least one of the following features is included: (1) The first mixing and the second mixing are both carried out in an internal mixer, and the rotation speed of the internal mixer is 25-30 r / min; (2) The temperature of the first mixing and the second mixing is 130-140° C.; (3) In the first mixing step: first, the remaining silicone rubber is mixed for 1-1.5 minutes, and then the structure control agent, surfactant, and ferrous oxide are added and mixed for 1.0-1.2 minutes; (4) The second mixing time is 2.5-3.5 min; (5) calendering the first rubber material after filtering and removing impurities using a three-roll calender to obtain the rubber sheet; (6) The thickness of the film is 1.2-1.5 mm.
7. The preparation method according to claim 4, characterized in that The preparation method further comprises subjecting the film to a static treatment before the third mixing, wherein the static treatment time is 8-24 hours.
8. The preparation method according to claim 4, characterized in that In step S2, at least one of the following features is included: (1) The third mixing is carried out in an internal mixer, and the rotation speed of the internal mixer is 20-25 r / min; (2) The temperature of the third mixing is 100-120° C.; (3) In the third mixing step: first mix the film for 1-2 minutes, then add the vulcanizing agent masterbatch and mix for 0.8-1 minute; (4) The second rubber material is subjected to calendering treatment by a three-roll calender to obtain the protective rubber.
9. A battery, characterized in that: The protective rubber comprises the protective rubber according to any one of claims 1 to 3 or the protective rubber prepared by the preparation method according to any one of claims 4 to 8.
10. The battery according to claim 9, characterized in that The battery comprises: A battery cell, wherein the edges of the upper end surface of the battery cell are sleeved with an annular rubber member, and the annular rubber member is made of the protective rubber; a shell, for accommodating the battery cell, wherein the shell has an opening; A top cover is welded to the shell to close the opening.